Root Cause Analysis Of Sustained Losses After Reputational Damage: A Case Study Of A Climate Change Company - Annisa Nurul Azizah; Santi Novani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The carbon credit market plays a crucial role in global goal of reaching "net-zero emissions" by 2050. However, such businesses within this market face serious challenges such as being vulnerable to credibility and financial issues. This study delves into the Kutub Selatan case, a prominent carbon credit project developer company that was suffered by reputational damage due to over-crediting allegations of the Kariba REDD+ project and received a lot of negative media sentiments. This reputational crisis led to a massive loss of revenue, client trust, and investor confidence, eventually manifesting as financial losses despite all recovery efforts. This research aims to determine the root cause of the company's financial losses, identify areas of revenue enhancement and cost efficiency, and explore the best scenario or strategy of attaining maximum profitability after a reputational damage. Using a System Dynamics approach, the study simulates various strategic alternatives, including differentiation, cost efficiency, and a combination of both, to compare their long-run financial performance in the long run. The finding suggests that differentiation is the optimal strategy in restoring profitability as it allows the company to rebuild market perception, enhance product value, and ultimately regain investor confidence.